Instrumentation with XP-Finisher as an enhancer for the disinfection of the root canal system – integrative review (Research, Society and Development, 2021)
The aim of this study was to present, through a literature review, the performance of XP-Endo Finisher as an aid in cleaning and disinfection of the root canal system. An electronic search in the Virtual Health Library (BVS), also known as the Regional Library of Medicine (BIREME), was carried out from april 2016 to May 2021, using the descriptors endodontics, disinfection and root canal therapy. A total of 76 works were found, of which 30 met the research criteria, which evaluated the instrument's action on the ability to remove smear layer, debris, biofilm and bacteria from the root canal system, in addition to comparing it to other complementary cleaning and disinfection systems. Taking into account the limitations of a literature review, the XPF presented satisfactory results. Thus, XPF was presented as a potential adjuvant instrument in the disinfection of root canal systems.